2002
DOI: 10.2355/isijinternational.42.1309
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior at the Intercritical HAZ of a 1.25Cr-0.5Mo Steel.

Abstract: Nowadays the preferential creep damage accumulation at the Intercritical HAZ (ICZ) leading to Type IV cracking has been a great concern for various industries. The ultimate failure of the welded components fabricated from ferritic steels often takes place at this particular region. Type IV cracking has been found in almost all the ferritic steel weldments so far, from a conventional 1.25Cr-0.5Mo steel to a modified 9Cr-1Mo steel. However, the mechanism of Type IV cracking has not yet been understood equivocall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…In the work on Type IV cracking for 0.5Cr-0.5Mo-0.25V steel by Walker et al, 4) it was found that cavitation preferentially took place at fine grains whose grain sizes were smaller than 5 mm. The similar finding was made in the work on 1.25Cr-0.5Mo steel by Fujibayashi et al 2) They found that 90 % of cavities were associated with fine grains which were smaller than 10 mm. It can be considered that fine grains at the ICZ are products of partial transformation during welding.…”
Section: T/t R ϭ1ϫsupporting
confidence: 72%
See 2 more Smart Citations
“…In the work on Type IV cracking for 0.5Cr-0.5Mo-0.25V steel by Walker et al, 4) it was found that cavitation preferentially took place at fine grains whose grain sizes were smaller than 5 mm. The similar finding was made in the work on 1.25Cr-0.5Mo steel by Fujibayashi et al 2) They found that 90 % of cavities were associated with fine grains which were smaller than 10 mm. It can be considered that fine grains at the ICZ are products of partial transformation during welding.…”
Section: T/t R ϭ1ϫsupporting
confidence: 72%
“…From the findings described above, it can be considered that the susceptibility to Type IV cracking is not determined simply by creep strength of base metal. It was pointed out that higher susceptibility could be arisen from higher non-metallic inclusion, 12) higher impurities 2,13) and morphology of fine grains, which became preferential cavity nucleus sites. 2) Further research on factors determining the sensitivity to this phenomenon should be conducted.…”
Section: Creep Strength Of Cross-weld Specimenmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier experimental works using a square cross-weld specimen were not necessarily successful since the ultimate failure mostly took place at the parent material on the pipe side in a ductile transgranular manner despite the growth of cavitational damage at the ICZ on the flange side. 6,7) The longest testing time for a square cross-weld specimen was 2 700 h. In order to generate Type IV cracking within reasonable testing duration, the specimen subjected to higher triaxiality has been employed. And it successfully generated Type IV cracking.…”
Section: Specimen Preparation and Testingmentioning
confidence: 99%
“…In addition, it was considered that the presence of notches would increase the rupture life of pipe parent due to reduction in the equivalent stress as found by the Finite Element Analysis (FEA). 7) All the creep tests were conducted in air with a constant load machine. Strain measurement for a spirally notched specimen during a test was not made.…”
Section: Specimen Preparation and Testingmentioning
confidence: 99%